PENGELOLAAN KONFLIK PADA PASANGAN PERNIKAHAN DI BAWAH UMUR DI DESA PESIK KECAMATAN SOJOL UTARA, KABUPATEN DONGGALA - Rahma (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2019)
This study aims to determine the management of conflict between couples who marry underage by using descriptive - qualitative research methods with the basis of case study research. Data collection techniques were carried out by means of observation and in-depth interviews. The informants in this study were 3 married couples who married underage, and the research location was in Pesik Village, North Sojol District, Donggala Regency. The results of this study indicate that the conflicts that occur in the households of these three married couples that cause conflict due to barriers to interpersonal communication, namely the absence of good communication, misunderstandings due to the lack of openness to partners often make couples suspicious and loss of trust. In addition, in managing conflict, informants prefer to avoid conflict so that it does not become a prolonged conflict, also present third parties to resolve conflicts in the household, provide solutions and also accept solutions from their partners or present third parties. There are five types of conflict management used, namely the avoidance type, the compromise type, the collaboration type, the accommodating type, and the competitive type. And the researcher sees that in resolving conflicts, informants use three types of the five types that exist in conflict management. Namely, the avoidance type was used by the informants Muslimin and Nasira, the compromise type by the informants Abhan and Rasmi, and the collaboration type by the informants Hamdan and Sukma, because the informants considered this type to be better in resolving conflicts in a household. These three types are more dominantly used by informants because this type of informants tries to control emotions by not prolonging the conflict, and looking for a way out of the conflict, to achieve a harmonious family.